Foot care behaviours and associated factors among patients with type 2 diabetes: a cross-sectional study - Ang, Chin-Siang (2024)
Background: As numerous studies highlighted the importance of maintaining proper foot care (FC) behaviours among individuals with diabetes to prevent complications, we sought to assess FC behaviours among patients with diabetes and to identify the factors associated with the practice of diabetic FC. Methods: We used a cross-sectional design and collected data through self-reported questionnaires administered to a sample of 586 patients from five medical centres. We conducted descriptive and inferential analyses to explore the relationships between potential risk and protective factors and FC behaviours. Results: Overall, 429 individuals (73.2%) had good FC behaviours, while 157 (26.8%) displayed poor FC behaviours. Furthermore, we identified eight influencing factors on FC behaviours, including smoking status, the availability of a caregiver, the presence of diabetic foot ulcers, amputation history, FC knowledge, subjective norms in diabetes selfcare behaviour, diabetes-related stress, and quality of life index values. The logistic regression analysis showed that current smokers were 60% less likely to practice good FC compared to non-smokers (odds ratio (OR) = 0.40; 95%; confidence interval (CI)= 0.22–0.73). Having a caregiver decreased the likelihood of practicing good FC by 50% (OR=0.52; 95% CI=0.33–0.84), while having diabetic foot ulcers doubled it (OR=2.65; 95% CI=1.26–5.54). Additionally, more FC knowledge increased the likelihood by 20% (OR=1.21; 95% CI=1.10–1.33), and higher diabetes-related stress increased it by 1.03 times (OR=1.03; 95% CI=1.02–1.05). Conclusions: Our findings underscore the interplay of various factors influencing FC behaviours among individuals with diabetes and call for targeted interventions and tailored strategies to improve FC practices in this vulnerable population.